Dental caries among children in Africa slums - Osadolor, Obehi. O; Osadolor, Aisosa .J; Amobi, Emmanuel (Nepal Mediciti Medical Journal, 2025)
Where we live is one of the social determinants of health. A slum is a residential area with poor buildings ,poor sanitation, overcrowding and a constant threat of homelessness and forced evictions. Families living in slums are a reflection of their household income. Dental caries is a significant public health problem among children, that can restrict academic activities in school, reduce play hours among children, and significantly affects quality of life when associated with pain and or swelling. After searching PubMed, African journals online and Google scholar by two independent investigators in January, 2025. The aim of this article was to review the available studies on the prevalence and associated factors of dental caries among children in Africa slums.The prevalence of dental caries among 2-17 years old slum-dwelling Kenyan children was 57.0%, 56.2% among 12-14 years old Kenyan children living in slum, with oral impacts on daily performance and oral health related quality of life and 17.8% among 5-16 years old slum-dwelling Nigerian children. Maternal and paternal educational level, child´s age, consumption of cariogenic meals, fluorosis and history of dental visits were associated with dental caries among the African children living in slums. Interventions for reducing the burden of dental caries among slum dwelling children could involve oral health education on avoidable risk factors for dental caries among slum dwellers, reduction of unmet oral healthcare needs and poverty eradication interventions in slums. Preventive interventions and oral health promotion activities for dental caries among children in Africa slums are recommended.